One Name, Two Genres: The Curious Case of Polish Encyclopaedias of Law - Rzepkowska, Agnieszka (Lexikos, 2025)
This study examines Polish legal reference works through systematic analysis of publications labelled as encyclopaedias of law, addressing a gap in legal metalexicography. It sheds some light on the typology and characteristics of such volumes. The library survey revealed two types of Polish encyclopaedias of law: lexicographic works with alphabetically ordered entries presenting fragmented knowledge and monographic works structured in chapters that resemble academic textbooks. In fact, in the majority of cases, only opening a given work lets the user learn what type of publication it is. The study describes 78 works published between 1842 and 2023 in terms of the publication year, the fields of law covered, size, scope and target users. The analysis demonstrates that lexicographic encyclopaedias of law predominantly specialise in specific legal fields and employ various systematisation techniques including cross-referencing and thematic indices, while monographic encyclopaedias of law primarily address general Polish law for educational purposes. An important observation emerging from this study is that monographic publications, despite their textbook-like structure, share fundamental characteristics with lexicographic ones and serve complementary knowledge-organizing functions that demonstrate lexicographic adaptability to diverse user needs within specialized domains. The findings challenge traditional lexicographic classification systems by suggesting that functional criteria may be more significant than formal structural features in understanding specialised lexicographic practice. Keywords: encyclopaedia of law, lexicography, Polish lexicography, legal language, LSP, special-purpose dictionary